Problems with adherence to treatment among adolescents with diabetes mellitus type 1 - Pires, Mônica Rocha; De Figueiredo Bani, Raissa Cazzonatto; De Lima, Graziele Zamineli; Haddad, Maria Isabela Ramos; Takamoto, Patricia Mayumi; Da Rocha Pires, Lúcia Alves; Manganaro, Márcia Marcondes; Croscioli, Márcia Regina Felippe Bueno; Fernani, Déborah Cristina Gonçalves Luiz; Vanderlei, Luiz Carlos Marques [UNESP]; Freire, Ana Paula Coelho Figueira; Pacagnelli, Francis Lopes (My University, 2016)
Introduction: Diabetes Mellitus type 1 (DM1) is a chronic degenerative disease with high impact on the lives of children and adolescents. The DM1 affects mainly children and young adults under 30 years old, with a predominance from 10 to 14 years old. As a chronic disease, involves changes in daily habits, being following the recommendations of health professionals one of the main conducts to achieve such changes, however, this follow-up is not easy and can directly infl uence the glycemic control and lead to complications. Objective: Identify the diffi culties of adolescent with DM1 to treatment adherence. The recommendations of this treatment are related to the blood glucose measurements, using a diet plan and insulin application. Methods: The study included 15 adolescent with DM1, of both genders, aged 10-19 years participating in a multidisciplinary group at an outpatient unit in São Paulo, Brazil, aged 13,93 ± 2.4 years, diagnosed with DM1 with an average time of 4.5 years. The following evaluations were employed:1) individual interviews for identifi cation and clinical characterization; 2) characterization of cardiovascular and metabolic parameters; 2) anthropometric assessment and 4) application of a questionnaire with questions about problems of blood glucose measurements, diet plan and insulin application. Data collection was performed before medical appointment with an endocrinologist in a hospital in São Paulo state. Results: The identifi ed diffi culties and cardio-metabolic variables showed the adolescents presented uncontrolled blood glucose levels, doing the rotation of insulin incompletely and face many daily diffi - culties to perform the appropriate treatment, being the most frequently reported the insulin application and proper nutrition. Conclusion: Adolescents with type 1 diabetes presented diffi culties in adherence to treatment, mainly o follow insulin treatment and proposals for changes in eating habits by following a diet. It is necessary that health professionals offer strategies and orientation to these individuals to improve the handling of their diffi culties that directly affect the course of the disease and leave them more susceptible to developing complications.
Keywords: Adolescent; Diabetes mellitus; Health assessment; Lifestyle